The spatial distribution of poverty in Vietnam and the potential for targeting - Minot, Nicholas; Baulch, Bob (International Food Policy Research Institute, 2002)
This paper combines household survey and census data to construct a provincial poverty map of Vietnam and evaluate the accuracy of geographically targeted anti-poverty programs. First, the paper estimates per capita expenditure as a function of selected household and geographic characteristics using the 1998 Vietnam Living Standards Survey. Next, these results are combined with data on the same household characteristics from the 1999 Census to estimate the incidence of poverty in each province. The results indicate that rural poverty is concentrated in ten provinces in the Northern Uplands, two provinces of the central Highlands, and two provinces in the Central Coast. Finally, Receiver Operating Characteristics curves are used to evaluate the effectiveness of geographic targeting. The results show that the existing poor communes system excludes large numbers of poor people, but there is potential to sharpen poverty targeting using a small number of easy-to-measure household characteristics.